Web-Based Student Extracurricular Value Monitoring Application - Richard Septiandi Karim; Aldi Hisyam Pratama; Wildan Ramdani A (Universitas Komputer Indonesia, 2022)
Extracurricular is a program of activities outside of the regular teaching and learning activity agenda prepared by the school for its students in order to develop the talents and interests of their students. In one of the upper secondary education institutions that provide several extracurricular activities to its students. The current problem is the lack of optimal extracurricular management in one of the educational institutions in Bandung, starting from the registration process, monitoring, to activity reports that still rely on conventional systems. The purpose of this research is to design a website information system to support the management of extracurricular activities at an institution in the city of Bandung by utilizing a database-based application. The research method used is data collection techniques and waterfall software development methods in designing applications. So that this research produces a website information system with several levels of access rights in accordance with the analysis carried out in the early stages of software development. The results of this information system, the parties involved as actors in extracurricular activities In one institution in the city of Bandung are very helpful in managing and monitoring extracurricular activities carried out So that this research produces a website information system with several levels of access rights in accordance with the analysis carried out in the early stages of software development. The results of this information system, the parties involved as actors in extracurricular activities In one institution in the city of Bandung are very helpful in managing and monitoring extracurricular activities carried out So that this research produces a website information system with several levels of access rights in accordance with the analysis carried out in the early stages of software development. The results of this information system, the parties involved as actors in extracurricular activities In one institution in the city of Bandung are very helpful in managing and monitoring extracurricular activities carried out.